2022
DOI: 10.3390/su14169899
|View full text |Cite
|
Sign up to set email alerts
|

Models and Methods of Formation of the Foresight-Controlling Mechanism

Abstract: The necessity of mechanisms for long-term forecasting and regulation of high-tech enterprise development strategies has been determined. This paper discusses how managers and designers can create models and methods for sustainability management mechanisms. The elements of novelty of this study and contribution to the existing theory of managing objects of socio-economic systems are: the development of the principle of a single mechanism of foresight-controlling, which made it possible to increase the efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In other words, for any values of the parameter (even arbitrarily large, but finite values) there will always be ω < ω 1 for which the values of the function constructed by Kotelnikov will differ from π, and there will always be ω > ω 1 , for which its values will be non-zero. Moreover, it is important to note that the indicated difference with increasing T does not tend to zero, but to approximately 0.281 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Mathematical tools for approximating functions make it possible to evaluate and more accurately control jump-like processes.…”
Section: New Methods For Approximating Step Processes: Functions By T...mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, for any values of the parameter (even arbitrarily large, but finite values) there will always be ω < ω 1 for which the values of the function constructed by Kotelnikov will differ from π, and there will always be ω > ω 1 , for which its values will be non-zero. Moreover, it is important to note that the indicated difference with increasing T does not tend to zero, but to approximately 0.281 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Mathematical tools for approximating functions make it possible to evaluate and more accurately control jump-like processes.…”
Section: New Methods For Approximating Step Processes: Functions By T...mentioning
confidence: 99%
“…Alyukov et al [5][6][7][8][9][10][11] make it possible to predict the influence of individual factors on the operation of an enterprise as a whole. V. Balakrishnan et al, A. Alabugin, and A. Nikitin showed that new control algorithms with increased accuracy significantly reduce the impact of forecasting errors [12][13][14]. In the economic ecosystems of a number of developing countries, researchers have identified the insufficient decarbonization of industrial territories.…”
Section: Introductionmentioning
confidence: 99%
“…This determined the need for high-tech transformations in terms of knowledge economy factors. The application of the theoretical and methodological model determined the development and implementation of methods for the functioning of the mechanism [9,117]. The operations of organizational design were implemented at the enterprise and in the Center for the Coordination of Interests of the Complex: a group of experts, researchers, and developers of the project for the formation and experimental functioning of the mechanism was created; external management consultants trained the company's specialists in mastering the characteristics of extended accounting for VUCA environmental factors, and coordination with standard management functions when integrating foresight and controlling functionality.…”
Section: Aspect 5: Aspect-based Approaches To Mathematical Modeling O...mentioning
confidence: 99%